"I Don't Think Kids Nowadays Feel Like They Have a Lot of Power": Exploring Teacher Civic Commitments in a National Online Letter Writing Project. (November 2022) - Gargroetzi, Emma C.; Garcia, Antero
This study investigates teacher participation in a national online youth civic letter writing project through the lens of teacher civic commitments. Drawing on in-depth interviews and survey data from teachers who participated in the Letters to the Next President 2.0 project, civic commitments are articulated through civic beliefs, learning goals, instructional enactments, and geopolitical context. With a generic shared belief in "youth voice, " teachers enacted the civic letter writing project through instructional activities that included (a) choice of topic, (b) publication, (c) reading letters from other youth, (d) research, (e) peer dialogue, and (f) connections beyond the Letters project. While beliefs appeared widely shared, divergence in learning goals and enactments led to distinct learning opportunities for students. With minimal research exploring the role of teachers in student civics learning, this study provides new insights to guide teacher preparation and ongoing teacher development in the realm of civics education.